The Exertional rhabdomyolysis with acute kidney injury after high-intensity CrossFit training in a young healthy male with dehydration and creatine supplementation: A case report - Neumann, Wojciech; Puchalski, Konrad; Lewowska, Maria Małgorzata; Labut, Bartłomiej; Kabak, Miraslau; Syska-lamb, Barbara; Kępa, Adrianna; Polakowska, Izabela; Pachcińska, Monika; Veer, Anna Sarolta (Quality in Sport, 2026)
High-intensity physical exercise leads to exertional rhabdomyolysis which causes muscle tissue destruction and myoglobin leakage that results in acute kidney damage. The development of exertional rhabdomyolysis with acute kidney injury has been linked to two main factors: dehydration and performing extreme physical activities. The main objective of this case report involves showing a person who developed rhabdomyolysis with kidney failure following their CrossFit workout at maximum intensity and we will examine the elements which increase the risk of this condition. A 25-year-old male patient developed rhabdomyolysis symptoms after his high-intensity CrossFit workout. The patient’s medical background, laboratory results and treatment progression were studied. The patient arrived at the hospital multiple hours after his exercise because his muscles were extremely painful and his urine had turned dark. The patient developed elevated creatine kinase levels and myoglobinuria and elevated serum creatinine which indicated acute kidney injury. The patient’s medical history showed he had not drunk enough water and he was taking creatine supplements at the same time. The patient received aggressive intravenous fluid treatment which brought his test results back to normal and restored his kidney function and he fully recovered within several days. Exertional rhabdomyolysis represents a rare but dangerous condition that occurs when people perform excessive physical activity which can cause their kidneys to fail. The treatment of this condition requires immediate medical care and strong therapeutic methods to prevent severe complications from occurring. The prevention of exertional rhabdomyolysis requires healthcare providers to monitor athletes for dehydration and high-intensity exercise during their training sessions.